If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -2) + (3x + 8) = 0 Reorder the terms: (-2 + 4x) + (3x + 8) = 0 Remove parenthesis around (-2 + 4x) -2 + 4x + (3x + 8) = 0 Reorder the terms: -2 + 4x + (8 + 3x) = 0 Remove parenthesis around (8 + 3x) -2 + 4x + 8 + 3x = 0 Reorder the terms: -2 + 8 + 4x + 3x = 0 Combine like terms: -2 + 8 = 6 6 + 4x + 3x = 0 Combine like terms: 4x + 3x = 7x 6 + 7x = 0 Solving 6 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 7x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 7x = 0 + -6 7x = 0 + -6 Combine like terms: 0 + -6 = -6 7x = -6 Divide each side by '7'. x = -0.8571428571 Simplifying x = -0.8571428571
| 12(y-x)= | | 2n+5n=26n | | 3(2x-5a)+4c=3x-6 | | 6x+3+4=7x+1 | | 8x+5=3x-26 | | 9-2(x+3)=3x-10 | | 3x-3=3(x+8) | | 4R-3x=N | | F(x)=2(g+3)2+4(g+3)+1 | | x+(x+3)+(2x)=23 | | 8z-2=62 | | X^4-4x^2-25x+100=0 | | (3y-y)-2(y-1)= | | 6(x-8)=x-3(7) | | 9x+3=9(4t+2)+3 | | 15x-17=73 | | 48=8y-5y | | 5t+4=3(2-t)+8 | | 2y-2(y-1)= | | 2x(2x)-x-3=0 | | 25.00x=49.95 | | 2x+55=-22 | | -43=-1x-13 | | 60.00x=42.95 | | 12k^2-k+7=0 | | 7x-(4x+10)=5 | | k^4-81= | | 3a^2+10a-2=0 | | 3c+2(3d+4)= | | .65=log(x) | | 4-d=-d(d-4) | | 200+16x=500-16x |